ABSOLUTE FREQUENCY EFFECTS IN SECOND LANGUAGE LEXICAL ACQUISITION. Issue 4 (September 2019) - Crossley, Scott A.; Skalicky, Stephen; Kyle, Kristopher; Monteiro, Katia
Abstract: A number of longitudinal studies of L2 production have reported frequency effects wherein learners' produce more frequent words as a function of time. The current study investigated the spoken output of English L2 learners over a four-month period of time using both native and non-native English speaker frequency norms for both word types and word tokens. The study also controlled for individual differences such as first language distance, English proficiency, gender, and age. Results demonstrated that lower level L2 learners produced more infrequent tokens at the beginning of the study and that high intermediate learners, when compared to advanced learners, produced more infrequent tokens at the beginning of the study and more frequent tokens toward the end of the study. Main effects were also reported for proficiency level, age, and language distance. These results provide further evidence that L2 production may not follow expected frequency trends (i.e., that more infrequent tokens are produced as a function of time).